2022
DOI: 10.1021/acs.organomet.2c00445
|View full text |Cite
|
Sign up to set email alerts
|

PNCNP Pincer Platinum Chloride Complex as a Catalyst for the Hydrosilylation of Unsaturated Carbon-Heteroatom Bonds

Abstract: A PNCNP pincer-ligated platinum(II) chloride complex [2,6-( t Bu 2 PNH) 2 C 6 H 3 ]PtCl (1a) was synthesized and fully characterized. Complex 1a was applied to the catalytic hydrosilylation of unsaturated carbon-heteroatom bonds. For comparison, the corresponding hydride complex [2,6-( t Bu 2 PNH) 2 C 6 H 3 ]PtH (1b) and the related POCOP pincer chloride complex [2,6-( t Bu 2 PO) 2 C 6 H 3 ]PtCl (1c) were also used to catalyze the reactions. It was found that 1a is a good catalyst for the hydrosilylation of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The platinum hydride complexes 1a and 2a were previously prepared and fully characterized by different experimental techniques including multinuclear NMR, FTIR, and X-ray crystallography analysis. , To make comparisons, some selected spectral and structural data related to the hydride auxiliary ligand in complexes 1a and 2a are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The platinum hydride complexes 1a and 2a were previously prepared and fully characterized by different experimental techniques including multinuclear NMR, FTIR, and X-ray crystallography analysis. , To make comparisons, some selected spectral and structural data related to the hydride auxiliary ligand in complexes 1a and 2a are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, complex 1a is expected to be more reactive against an electrophilic reagent. This is consistent with our previous observation that benzaldehyde is far easier to react with complex 1a to form the corresponding benzyloxide complex compared to complex 2a . , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have cited additional references within the Supporting Information. [72][73][74][75][76][77][78][79][80][81][82][83][84][85]…”
Section: Supporting Informationmentioning
confidence: 99%
“…Compared to other benzene-based PYCYP-type pincer complexes, the catalytic application of the PNCNP-type complexes has far less been explored. We recently investigated the structure, reactivity, and catalytic application of some group 10 metal PNCNP pincer complexes . We found that the palladium hydride complex [2,6-( t Bu 2 PNH) 2 C 6 H 3 ]­PdH ( 1b ) is a good catalyst for both direct hydration of nitriles to primary amides and dehydrogenation of methanol to formaldehyde under mild conditions .…”
Section: Introductionmentioning
confidence: 99%